Högskolans språk och mitt eget. En studie av nyantagna lärarstudenters förhållningssätt till skrivande, skriftspråket på högskolan och den egna skrivkompetensen - Aldrin, Emilia Sturm; Eklund, Monica; Peter, Heike (Högre utbildning, 2020)
This article explores how a heterogenous group of first year university students perceive writing in general, academic writing in specific, as well as their own writing proficiency. A questionnaire (n 93) was created basing on theories on academic literacy and writing psychology. The results show varying attitudes among the students which highlight questions of the dimensions of writing, identity and group affiliations. Gender was of little importance, whereas age and self-stated writing skills correlated to some extent with the results. The small scale of the study does not permit far-reaching conclusions, but the results indicate attitudes that could have importance for the development of academic literacy. The study can be used as a start of departure for interventions that facilitate for groups with different backgrounds to participate in higher education.